ANALYSIS OF FACTORS THAT INFLUENCE THE LOW UTILIZATION OF HEALTH SERVICES IN INPATIENT ROOMS IN THE COMMUNITY IN RSUD TUAN RONDAHAIM PEMATANG RAYA KABUPATENSIMALUNGUN IN 2019 - Nerdy, Nerdy; Siagian, Nurul; Fahdi, Firdaus (Jurnal Inovasi Kesehatan Masyarakat, 2021)
The hospital is a center for public health services in an effort to prevent, restore and cure diseases and improve health status. The increasing level of community life is the increasing also the demands of the community on quality of health. To find out factors that effect the low utilization of health services in the hospitalization of community in RSUD Tuan Rondahaim Pamatang Raya. The number of sampel was 97 responden who get 2.777 hospitalization in that hospital in 2017.The type of research used is analytic survey research with cross secsional design,namely research conducted at the same time but with different subject. The results showed that there was a significant influence between sex and service utilization, The level of education has a significant effect on service utilization. Income has a significant influence with the utilization of health services. Hospital facilities had a significant influence with the utilization of health services. The distance to the service location had a significant influence with the utilization of health services, trust with the utilization of health services. Types of illness with utilization of health services. Trust is the most dominant factor in the utilization of health services with a value of RP = 25,260 (95% CI: 4,022-158,645), it means that the tendency of respondents to believe in a good health service place is 25,260 times greater than those who do not believe in a health service in a hospital. There was no significant influence between age, occupation and service costs with the utilization of health services (p> 0.05).It is expected that hospitals will maintain and provide the best services, and continue to make improvements regarding the availability of more complete facilities, types or variations of health services.